Fast Multiple Organs Detection and Localization in Whole-Body MR Dixon Sequences - Pauly, O.; Glocker, B.; Criminisi, A.; Navab, N.; Mateus, D.; Moller, A. Martinez; Nekolla, S.; Criminisi, Antonio; Glocker, Ben (MICCAI 2011 - 14th International Conference on Medical Image Computing and Computer Assisted Intervention, 2011)
Automatic localization of multiple anatomical structures in medical images provides important semantic information with potential beneﬁts to diverse clinical applications. Aiming at organ-speciﬁc attenuation correction in PET/MR imaging, we propose an efﬁcient approach for estimating location and size of multiple anatomical structures in MR scans. Our contribution is three-fold: (1) we apply supervised regression techniques to the problem of anatomy detection and localization in whole-body MR, (2) we adapt random ferns to produce multidimensional regression output and compare them with random regression forests, and (3) introduce the use of 3D LBP descriptors in multi-channel MR Dixon sequences. The localization accuracy achieved with both fern - and forest - based approaches is evaluated by direct comparison with state of the art atlas-based registration, on ground-truth data from 33 patients. Our results demonstrate improved anatomy localization accuracy with higher efﬁciency and robustness